Evaluation of Rayleigh Damping Coefficients for Laminated Rubber Bearing Components Using Finite Element and Experimental Modal Analysis - Yusuf, Ahmad Idzwan; Mohd Amin, Norliati; Yunus, Mohd Azmi; Abdul Rani, Muhamad Norhisham (International Journal of Integrated Engineering, 2019)
Laminated rubber bearing is a significant device found in structures such as bridges and buildings. It is used to isolate the foundation and the superstructure from seismic loads. Since it is made up from a combination of rubbers and steel plates in alternate layers which make the laminated rubber bearing a complex material, the measurements of damping of the laminated rubber bearing is difficult in practice. Damping is a dissipation of energy or energy losses in the vibration of the structure when the structures are excited with external dynamic loading. An accurate value of damping is very important as damping plays a crucial role in fixing the borderline between stability and instability in many structural systems. Therefore, it is essential to determine the accurate value of damping in structural analysis. Finite element and experimental modal analysis is one of the methods that can be used to determine dynamic properties including damping in any structures. Hence, the main objectives of this research are to determine the natural frequencies, mode shapes, Rayleigh’s damping coefficients, α and β and to evaluate the performance of the laminated rubber bearing components i.e. steel and rubber plates using finite element and experimental modal analysis. Based on the finding, the finite element modal analysis with the added Rayleigh’s damping coefficients α and β shows a good agreement with the experimental modal analysis in term of natural frequencies and mode shapes. The value of natural frequencies reduces after the Rayleigh’s damping coefficients are added into the finite element modal analysis and the minimum and maximum displacement are found to be unaffected by the Rayleigh’s damping coefficients for rubber plate. It can be concluded that modal analysis method can be used to estimate the accurate values of damping ratio and to determine the Rayleigh’s damping coefficients α and β as well.